2015
DOI: 10.1099/ijsem.0.000641
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium luticellarii sp. nov., isolated from a mud cellar used for producing strong aromatic liquors

Abstract: A strictly anaerobic, Gram-stain-positive bacterium, designated FW431 T , was isolated from a mud cellar used for producing strong aromatic Chinese liquors. The strain was able to produce butanoic acid, an important component of the aroma style of Chinese liquors. Cells of strain FW431 T were straight or slightly curved rods with a polar endospore and peritrichous flagella. The major cellular fatty acids (.10 % of the total) were C 16 : 0 , C 18 : 1 v9c and C 18 : 0 . Biolog assays indicated that the strain pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Moreover, a caproate producer recently isolated in our laboratory, Clostridiales bacterium isolate BL-3, is also closely related to C. luticellarii (Liu et al, 2020b,c). C. luticellarii is closely related to C. ljungdahlii (a solventogen and syngas fermenter) and C. kluyveri (a chain elongator) (Wang et al, 2015;de Smit et al, 2019). Moreover, it is important to highlight that the fact that no ethanol accumulated in our experiments should not exclude the possibility of this ED being the one intermediating the H 2 -to-caproate through interspecies transfer.…”
Section: Key Players In H 2 -Aided Chain Elongationmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, a caproate producer recently isolated in our laboratory, Clostridiales bacterium isolate BL-3, is also closely related to C. luticellarii (Liu et al, 2020b,c). C. luticellarii is closely related to C. ljungdahlii (a solventogen and syngas fermenter) and C. kluyveri (a chain elongator) (Wang et al, 2015;de Smit et al, 2019). Moreover, it is important to highlight that the fact that no ethanol accumulated in our experiments should not exclude the possibility of this ED being the one intermediating the H 2 -to-caproate through interspecies transfer.…”
Section: Key Players In H 2 -Aided Chain Elongationmentioning
confidence: 86%
“…With relatively high abundances in all communities, the genus Clostridium sensu stricto 12 thrived particularly in communities A and C after lactate and ethanol addition (Figure 8). So far, hydrogenotrophy and caproate production have not been reported as functions of C. luticellarii (Wang et al, 2015). However, its genome harbors typical genes of the Wood-Ljungdahl pathway (Poehlein et al, 2018) and C. luticellarii was the main candidate to elongate propionate to valerate and to produce i-butyrate in a recent study (de Smit et al, 2019).…”
Section: Key Players In H 2 -Aided Chain Elongationmentioning
confidence: 99%
“…Clostridium luticellarii is a known butyrate-producing strain (Additional file 1: Table S11) within the Clostridium sensu stricto 12 genus. It shares the highest similarities with Clostridium ljungdahlii and Clostridium kluyveri [44]. C. luticellarii is the prime candidate for performing the methanol-based chain elongation, which well fits its similarities to a Wood–Ljungdahl-harbouring ( C. ljungdahlii ) microorganism and a reverse β-oxidation-harbouring ( C. kluyverii ) microorganism.…”
Section: Discussionmentioning
confidence: 99%
“…Other dominant genera included Weissella, Pediococcus ( Yang J.-G. et al, 2017 ), Lactobacillus, Acetobacter ( Ming et al, 2013 ) from daqu; and Sporolactobacillus, Clostridium, Mycobacterium , and Flavobacterium from pit mud ( Yue et al, 2007 ). In addition, six new species of bacteria [ Paenibacillus vini ( Chen et al, 2015 ), Bacillus vini ( Ma et al, 2016 ), Lysobacter zhanggongensis ( Zhang et al, 2017 ), Clostridium swellfunianum ( Liu et al, 2014 ), C. luticellarii ( Wang et al, 2015 ), and C. liquoris ( Yin et al, 2016 )] were detected and identified from the SFB ecosystem.…”
Section: Microbial Diversity Of Cultured Microorganismmentioning
confidence: 99%